Melhoria da comunicação no desenvolvimento distribuído de software baseado em Scrum - Santos, Leonardo Sanches dos (2016)
Software development between geographically distributed teams has acquired relevance due to interests of organizations, project-related costs, looking for multidisciplinary and specialized professionals or aiming to expand the coverage of its customers, serving them in a globalized form. However, despite the existing benefits, there are some difficulties originated from the distribution of teams that are inherent in the temporal and geographic dispersion. These difficulties include the cultural, linguistic, temporal among others, which affect the quality of communication and consequently interfere with the mutual comprehension between the teams which develop the same software project. Thus, the aim of this work is to present an improvement in the process of distributed software development (DSD) based on Scrum, capable to minimize interference and information losses, decentralization of knowledge in specific people and improve the communication flow and dissemination of information. A real case was discussed and as for the development of this work the action research was the approach employed in this study. In this scenario, problems originated from inefficient communication between their actors and demanded that the development of this research present several iterations and feedbacks in order to reach its maturity. Improved communication has been achieved and is the main contribution of this work.